Localisation of ventricular septal defects by simultaneous display of superimposed colour Doppler and cross sectional echocardiographic images. - Ortiz, E (1985)
Precise non-invasive localisation of the site of a small ventricular septal defect was attempted using a new technique that simultaneously combines conventional cross sectional echocardiography with a Doppler system by superimposing the colour coded direction and velocity of blood flow directly on to real time ultrasound images. Twenty three patients with unoperated ventricular septal defects and a further eight after surgical closure were studied; 12 children with normal hearts served as controls. A colour coded blood flow jet entering the right ventricle during systole was identified in all 23 unoperated patients, in 11 of whom the defect was too small to be visualised by conventional cross sectional echocardiography. The colour Doppler technique precisely located 19 perimembranous and five trabecular defects (one patient had two defects). Five of the postoperative patients were without clinical evidence of a significant shunt but had pansystolic murmurs. In each of these five, trans-septal shunt blood flow as demonstrated by colour Doppler images whereas in only three of these patients was the residual defect large enough to be visualised by conventional cross sectional echocardiography. Three postoperative patients had no murmurs and showed no residual shunt on colour Doppler images. This was confirmed at cardiac catheterisation. There were no false positive results among the controls. This technique is useful for the more accurate diagnosis and location of ventricular septal defects and may help in assessing their natural or surgical closure.